Managing injury and other setbacks in sport: experiences of (and resources for) high-performance women athletes - Mosewich, A. D.; Crocker, P. R. E.; Kowalski, K. C. (Qualitative Research in Sport, Exercise and Health, 2014)
Regardless of the level of sport competition, setbacks are inevitable and can promote stress, requiring effective coping skills. Well-developed coping skills are required for athletes to not only reach their performance potential, but also to have healthy sport experiences. The purpose of the present study was to further explore setbacks and coping in sport experienced by a group of high-performance women athletes. Through exploration of their experiences, relevant setbacks and resultant coping efforts were identified, providing insight into the effectiveness of resources for this population, as well as areas of stress and coping deserving more attention. Using a phenomenological orientation, five high-performance women athletes were interviewed about their experiences with setbacks in sport. Thematic analysis revealed that poor performance, performance plateau and injury were common setback experiences. Managing setbacks involved having a positive approach, dealing with self-criticism, using social support and striving for balance. Results speak to the importance of considering the implications and challenges presented by setbacks when attempting to promote effective coping among athletes. Additionally, unique approaches, such as fostering mindful or self-compassionate perspectives, may positively add to coping skill resources through targeting issues that the athletes identified as particularly challenging.